PENGARUH INTERNET FINANCIAL REPORTING TERHADAP REAKSI PASAR SEBELUM DAN SESUDAH INTERNET FINANCIAL REPORTING - Immanuela, Intan; Purbandari, Theresia (Widya Warta, 2016)
The purpose of this study demonstrate empirically that the Internet Financial Reporting (IFR) effect on abnormal return, abnormal return before and after applying IFR different, and the volume of stock trading company before and after applying IFR different. Samples were determined using purposive sampling technique . Based on specific criteria, manufacturing companies listed in Indonesia Stock Exchange in 2013 as sample 115. To test the hypothesisÂ  1 used a simple linear regression analysis, while for the hypothesis 2nd and 3rd use different test . The results showed that IFR had no effect on abnormal return, abnormal return before and after applying IFR is no different, and the volume of stock trading company before and after applying IFR is no different.